Presenting the professional thinking model of employees based on the dimensions of ambivalence and psychological empowermen - Abdolmajid Kord; Mansur Garkaz; Alireza Maetoofi; Ali khuzin; Alireza Hasan Maleki (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is to present the professional thinking model of employees based on the dimensions of ambivalence and psychological empowerment. The research method is applicable in terms of its purpose, hypothesis-deductive in terms of the approach, and descriptive-exploratory in terms of the research implementation method. The statistical population of the research includes 1100 people from the public accountant's community of Iran, 297 of whom were selected as a sample using Morgan's table, and the sampling method is available. The research tool is a researcher-made questionnaire. In order to determine the reliability of the questionnaires, Cronbach's alpha method was used using SPSS software, and composite reliability was determined by using SMART PLS software. Also, confirmatory factor analysis was used to show the reliability of the questionnaire. The results showed that there is a relationship between the dimensions and components of professional thinking and ambivalence. There is a relationship between the dimensions and components of professional thinking and empowerment. The obtained value for GOF is 0.51, which confirms the very good fit of the overall model. Extended abstract Introduction Innovations shape and change our lives and we often welcome these innovations. Innovation and efficiency are not necessarily incompatible. A company that pursues high degrees of innovation and efficiency follows a two-pronged strategy. The word ambivalence is composed of two Latin words meaning two-way and skill. Ambivalence is the ability of an organization to address two organizationally incompatible goals equally (Ghorehjili et al, 2019). At the psychological and behavioral level, people who have the ability to use both hands with equal skills are called ambidextrous people (Mercedes et al, 2016). Organizational ambidexterity is used as a metaphor to define organizations that seek to effectively meet current demands by controlling their current activities, while expanding their abilities to anticipate and adapt to future changes (Mohammad F et. et al., 2019). One of the most important concerns of the successful economic enterprises of the world is to collect educated and intelligent human capital who are able to create positive changes and developments in the relevant organizations. Therefore, equipping and preparing the mentioned resources in order to face the changes and create the context for positive changes in organizations is of special importance. Many thinkers have recognized the solution to this problem (preparation of human resources to face the changes and progress of the organization) by empowering the human force, and have tried to provide the necessary background for training capable employees (Kurdi, 2023). Empowerment is from a psychological perspective; it means creating an inner sense in people who can make independent decisions in their work process. In this view, people's attitude and perception of their work duties and their role in the organization is considered. Psychological empowerment means creating the necessary conditions to improve people's motivation in performing tasks, through developing a sense of competence or reducing the feeling of helplessness in them (Sarboland, 2019). Economic enterprises are formed with the aim of earning and profiting and continue their activities. Audit institutions also need income to continue their activity. Therefore, organizations can be considered successful that use their maximum capacity (managers' thinking) to generate income. Therefore, according to the mentioned points, the researcher is trying to answer the main question: what is the professional thinking model of employees based on the dimensions of ambivalence and psychological empowerment? Theoretical Framework Professional thinking Professional thinking is the dimension that shows the individual's movement within the professional framework and principles, that is, the individual's point of view towards regular and logical activities in the profession from which he earns money, and mental activities that are reflective for solving professional tasks. The quality of professional activity or the level of professionalism depends on the type of thinking (Jafari & Safari, 2023). Ambivalence Ambivalence means the organization's ability to achieve radical and gradual innovation at the same time as exploration and exploitation, stability and transition in organizational adaptation, and efficiency and flexibility in organizational design. Ambivalent organizations and in general, attention to organizational ambivalence is inevitable in today's dynamic world (Eskandari et al, 2022). Empowerment Empowerment from a psychological perspective means creating an inner sense in people who can make independent decisions in their work process. In this view, people's attitude and perception of their work duties and their role in the organization is considered. Psychological empowerment means creating the necessary conditions to improve people's motivation in performing tasks, through developing a sense of competence or reducing the feeling of helplessness in them (Sarboland, 2019). Guohong et al, (2022) studied about "creating team ambidexterity and the effects of leader's thinking and employee performance". Their findings showed that a leader's thinking can help facilitate team ambidexterity (a leader's dialectical thinking positively affects team ambidexterity). And team ambidexterity has a positive relationship with employee performance, which in turn improves employee performance, and those teams whose members have a strong team identity and whose leader has high thinking will benefit the most from team ambidexterity. Bagher Pur et al, (2022) investigated the effect of the source of control on the relationship between auditors' psychological empowerment and audit quality. The results of the research showed that the psychological empowerment of auditors has a positive and significant relationship with audit quality. Also, the results showed that by increasing auditors' internal control source, the positive relationship between psychological empowerment and audit quality improves. In other words, employees who have high psychological empowerment and high internal control source perform the audit with the highest quality. Research methodology The research method is applicable in terms of its purpose, hypothesis-deductive in terms of the approach, and descriptive-exploratory in terms of the research implementation method. The statistical population of the research includes 1100 people from the public accountant's community of Iran, 297 of whom were selected as a sample using Morgan's table, and the sampling method is available. The research tool is a researcher-made questionnaire. Research findings In order to determine the reliability of the questionnaires, Cronbach's alpha method was used using SPSS software, and composite reliability was determined by using SMART PLS software. Also, confirmatory factor analysis was used to show the reliability of the questionnaire. The results showed that there is a relationship between the dimensions and components of professional thinking and ambivalence. There is a relationship between the dimensions and components of professional thinking and empowerment. The obtained value for GOF is 0.51, which confirms the very good fit of the overall model. Conclusion The current research was conducted with the aim of providing a professional thinking model of employees based on the dimensions of ambivalence and psychological empowerment. This finding is in agreement with the research findings of Guohong et al, (2022), Bagher Pur et al, (2022), Eskandari et al, (2022), Ilani (2021), Mehr Sabet et al, (2021), Shahabi Nasab et al, (2021), Bahramzadeh (2020), Bani Mahd et al, (2020), Alipur et al, (2020), and Mohammad F et al, (2019). Guohong et al, (2022) showed that a leader's thinking can help facilitate team ambidexterity (a leader's dialectical thinking positively affects team ambidexterity). And team ambidexterity has a positive relationship with employee performance, which in turn improves employee performance, and those teams whose members have a strong team identity and whose leader has high thinking will benefit the most from team ambidexterity. According to the results of the research, the following suggestions were made: It is suggested that managers of organizations by addressing issues such as life conditions, deficiencies, psychological and personality factors, people's ideals and such things that affect people's professional thinking while strengthening people's professional thinking, help the organization extract its existing capabilities and discover new opportunities at the same time; and the ability of the organization to achieve radical and gradual innovation explore and exploit; at the same time, and stability and transfer in organizational adaptation and efficiency and flexibility in organizational design.take place.